Snow Road Construction by Layered Compaction-Construction and Maintenance Guide. - Barthelemy,J. L. (1975)
The use of rubber-tired vehicles in polar regions greatly speeds the movement of cargo and personnel. However, in areas of perennial snow, roads must be provided. Heavy-haul, wheeled transportation equipment, in particular, requires high-strength snow roads while operating on deep snow fields. Specially processed, elevated snow roads can provide dependable service for 2 years or more. This construction guide outlines those procedures necessary to build and preserve snow roads by means of layered compaction, the simplest and most rapid technique developed by CEL. In this process, the roadbed is built up to a desired elevation by successive compaction of 4-inch layers of snow. A modified rotary snowplow is used to gather, process and deposit the construction material.